Analisis Kinerja Ramp Handling Untuk Mencapai On Time Performance Maskapai Wings Air Pada PT. Merpati Angkasa Abadi Di Bandar Udara Sultan Muhammad Kaharuddin Sumbawa - Arif Rahman; Yuniar Istiyani (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
Airlines must always improve passenger services on the ground. One of its services is the determination of time or On Time Performance which is a benchmark for the trust of service users who are the choice to travel. There are obstacles that become obstacles in achieving On Time Performance, namely worsening uaca, inadequate airport facilities, traffic and others. This study aims to determine the performance of Ramp Handling in handling aircraft at Wings Air at PT. Merpati Angkasa Abadi at Sultan Muhammad Kaharuddin Airport Sumbawa and for 2.knowing the stipulation of aircraft departure time on Wings Air airline At PT. Merpati Angkasa Abadi at Sultan Muhammad Kaharuddin Airport Sumbawa. This research is qualitative with data obtained from observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and conclusions. This research will be conducted in July 2023 at PT. Merpati Angkasa Abadi at Sultan Muhammad Kaharuddin Airport Sumbawa. The result of this study is the performance of Ramp Handling in handling aircraft is to ensure all tools, needs and employees are ready to be positioned with their respective duties, and monitor the weather for the aircraft in order to land. In addition, the Ramp Handling Unit serves as a liaison between operational activities at the facility and operational activities at the terminal. To provide or ensure all activities on the aircraft and in the terminal run properly. The achievement of On Time Performance has been maximally optimized according to the time given by the company for 20 minutes the aircraft while on the ground, the Ramp unit makes excellent use of this time. The achievement of punctuality has been carried out optimally starting from before the plane landed. All jobs such as, helping cabin crew pick up garbage from the plane, communicating with pilots, and communicating with engineers to ensure the condition of the engine to raise passengers into the plane.